ANALYSIS OF PROFITABILITY RATIO AS A TOOL TO ASSESS FINANCIAL PERFORMANCE AT PT. TIGA PILAR SEJAHTERA FOOD TBK - Ayi Hendriawan; Kurniawati Kurniawati; Danang Apriliyanto (CV Pena Jaya Pers, 2024)
Profitability ratio is a ratio to assess the company's ability to generate profits during a certain period. The types of ratios used in measuring company profitability are using gross profit margin, net profit margin, return on assets and return on equity. The purpose of this research is to analyze the financial performance of PT Tiga Pilar Sejahtera Food Tbk through profitability ratios. The method used in this research is descriptive qualitative, which is a method or way to conduct research on profitability ratio analysis to assess financial performance at PT Tiga Pilar Sejahtera Food Tbk. The results showed that gross profit margin increased, net profit margin decreased, return on assets decreased and return on equity decreased. Based on the results of the calculation of financial performance at PT Tiga Pilar Sejahtera Food Tbk during 2014 and 2015 when viewed from the pofitabilitas ratio is less efficient. The company is unable to evaluate or maintain the success of past financial performance.